2007
DOI: 10.1097/ajp.0b013e31802be869
|View full text |Cite
|
Sign up to set email alerts
|

An Interdisciplinary Expert Consensus Statement on Assessment of Pain in Older Persons

Abstract: This paper represents an expert-based consensus statement on pain assessment among older adults. It is intended to provide recommendations that will be useful for both researchers and clinicians. Contributors were identified based on literature prominence and with the aim of achieving a broad representation of disciplines. Recommendations are provided regarding the physical examination and the assessment of pain using self-report and observational methods (suitable for seniors with dementia). In addition, reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
391
1
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 496 publications
(409 citation statements)
references
References 342 publications
6
391
1
11
Order By: Relevance
“…In addition, its properties were not age-related. Moreover, according to a study of literature review, the NRS was easily to understand and recommended for pain assessment in elderly including those with none to mild or moderate CI (Hadjistavropoulos et al, 2007). Ware, Epps, Herr, and Packard (2006) supported the convergent validity of the NRS and its test-retest reliability at a 2-week interval in older minority adults including elderly with CI.…”
Section: Unidimensional Assessment Tools Based On Self-reportmentioning
confidence: 85%
See 3 more Smart Citations
“…In addition, its properties were not age-related. Moreover, according to a study of literature review, the NRS was easily to understand and recommended for pain assessment in elderly including those with none to mild or moderate CI (Hadjistavropoulos et al, 2007). Ware, Epps, Herr, and Packard (2006) supported the convergent validity of the NRS and its test-retest reliability at a 2-week interval in older minority adults including elderly with CI.…”
Section: Unidimensional Assessment Tools Based On Self-reportmentioning
confidence: 85%
“…The VDS was the most easily understandable and preferred scale and was suitable for all but patients with most severe CI; convergent validity of the VDS was high except in patients with severe CI (Closs et al, 2004). Moreover, according to a study of literature review, the VDS has been shown to be the most preferred and understandable tool and is recommended for pain assessment in illiterate patients and the patients with none to mild or moderate CI (Hadjistavropoulos et al, 2007). However, construct validity of the VDS was a little less strong in younger and older adults (Peters et al).…”
Section: Unidimensional Assessment Tools Based On Self-reportmentioning
confidence: 97%
See 2 more Smart Citations
“…The physical examination should target the musculoskeletal and neurological systems which are the most frequent causes of chronic pain 33 and should comprise the following:…”
Section: Physical Examinationmentioning
confidence: 99%